Food Safety: High-Risk Foods - Jennifer Hillan (EDIS)
FCS8802, a one-page fact sheet by Jennifer Hillan, features a crossword puzzle on the subject of food safety that will help elders understand which foods may be high-risk. Published by the UF Department of Family, Youth and Community Sciences, April 2007.